Impact of obesity in the health of the female children and adolescents - Cabello Morales, Emilio Andrés (2018)
There is scientific evidence of the association between adult obesity and the metabolic syndrome, type 2 diabetes mellitus, cardiovascular disease and premature death due to myocardial infarction and cerebrovascular disease. There is also evidence on the beginning of atherosclerosis in childhood, but the effect of childhood and adolescent obesity on young adults and adults it is not clearly defined as well as its association with higher morbidity and mortality by non communicable chronic diseases. It was our interest to review and analyze obesity in children and adolescents as a risk factor to develop atherosclerosis, metabolic syndrome, type 2 diabetes mellitus, cardiovascular disease and premature death in youth and adulthood. Conclusions: Despite no consensus to define obesity in children and adolescents there is a growing tendency to its prevalence in the last decades. The obesity that starts in early life tends to perpetuate. There is no consensus to define metabolic syndrome in children but it is necessary to detect and treat separately the risk factors. There exists significant association with type 2 diabetes mellitus, cardiovascular disease and death due to myocardial infarction and cerebrovascular disease in the adult. Intervention on obesity and other risk factors that start early in life significantly decreases the occurrence of adult cardiovascular disease.